Avaliação das características cognitivas de pacientes com distonia cervical idiopática: um estudo transversal com grupo controle - Henrique Soares Dutra Oliveira (2020)
Introduction: The understanding that dystonia is a condition that involves not only motor symptoms, but also non-motor elements is relatively recent information. Several authors have reported that patients with isolated dystonia have cognitive abnormalities, although the reports have been somewhat inconsistent and some conflicting findings. Objectives: To investigate the cognitive performance and the neuropsychiatric profile of a sample of patients with idiopathic adult-onset cervical dystonia (CD), to determine the occurrence of neuropsychiatric abnormalities and their influence on cognitive performance and to confront the frequency of cognitive disorders in the studied sample with data from the current literature. Methods: The present study is a cross-sectional study, with a control group, performed on selected patients on consecutive outpatient visits at the Movement Disorders Clinic of the Faculty of Medicine of the Federal University of Minas Gerais. Thirty individuals were evaluated, including 15 patients with idiopathic CD (case group) and 15 individuals paired with each member of the case group considering sex, age, and years of schooling. Clinical assessments followed a pre-established and fixed order that involved the testing of global cognition, executive functions, verbal and non-verbal memory, visuospatial and visuoconstructive skills, verbal fluency and neuropsychiatric symptoms (depression and anxiety). Results: Regarding the assessment of cognitive skills, no significant differences were identified between the two groups for most variables, except for Phonological Verbal Fluency (F-A-S), in which there were significantly lower results in the case group (p 0.001). There was a significant positive correlation between disease duration and duration of botulinum toxin application and total errors and non perseverative errors in Berg Card Sorting Test (BCST-64). On the other hand, the time of use of botulinum toxin correlated significantly in a negative way with BCST-64 (total of categories and attempts to complete the first category). Conclusions: The results of this study suggest that individuals with isolated idiopathic adult-onset CD have cognitive impairment confined to verbal fluency when compared to healthy controls matched by sex, age and education. As for neuropsychiatric symptoms, especially anxiety and depression, dystonic patients did not differ from controls. Additional research using larger samples and more sensitive neuropsychological tools, preferably accompanied by functional neuroimaging and neurophysiological assessment, are vital.